2021
DOI: 10.1097/ta.0000000000003235
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trauma Composite Score is a more reliable predictor of mortality than Injury Severity Score in pediatric trauma

Abstract: BACKGROUND:The equivalent Injury Severity Score (ISS) cutoffs for severe trauma vary between adult (ISS, >16) and pediatric (ISS, >25) trauma.We hypothesized that a novel injury severity prediction model incorporating age and mechanism of injury would outperform standard ISS cutoffs. METHODS:The 2010 to 2016 National Trauma Data Bank was queried for pediatric trauma patients. Cut point analysis was used to determine the optimal ISS for predicting mortality for age and mechanism of injury. Linear discriminant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…This study also showed that the prevalence and in-hospital mortality of severely injured patients aged 55–64, 65–75 and ≥75 years increased stepwise. On the other hand, previous studies suggested that the ISS cut-off of ≥16 in adult patients was equivalent to a cut-off of ≥26 in paediatric patients aged <16 years 14 15. This study showed different results from those of a previous study,15 where the in-hospital mortality of paediatric patients aged 0–4 years with an ISS ≥26 was high (17.7%) and that of paediatric patients aged 5–14 years with an ISS ≥26 was low (10.9%), as shown in figure 2.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This study also showed that the prevalence and in-hospital mortality of severely injured patients aged 55–64, 65–75 and ≥75 years increased stepwise. On the other hand, previous studies suggested that the ISS cut-off of ≥16 in adult patients was equivalent to a cut-off of ≥26 in paediatric patients aged <16 years 14 15. This study showed different results from those of a previous study,15 where the in-hospital mortality of paediatric patients aged 0–4 years with an ISS ≥26 was high (17.7%) and that of paediatric patients aged 5–14 years with an ISS ≥26 was low (10.9%), as shown in figure 2.…”
Section: Discussioncontrasting
confidence: 77%
“…1530 (13) 2106 (15) 3053 (15) 3548 (10) Upper extremity injury with AIS ≥3 6562 (6) 57 (5) 590 (14) 581 ( 5) 522 ( 7) 711 ( 7) 849 (7) 798 (6) 1026 (5) 1428 ( 4)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed uses include intensive care unit admission guidelines, 17,18 study inclusion criteria, 25 and risk prediction 21 . It has also been incorporated as one component of multifaceted mortality prediction tools 16,21,26 …”
mentioning
confidence: 99%
“…We have now demonstrated the failures of universal ISS cutoffs in both adult and pediatric trauma patients. 19 As ISS is a commonly used metric for trauma outcomes research and quality improvement metrics, it is important that we begin to reconsider how injury severity is measured and used among trauma patients. Injury Severity Score has previously been to be an imperfect metric as it does not account for mechanism of injury, age, and presenting physiology.…”
Section: Discussionmentioning
confidence: 99%